Strategi Dinas Perikanan dalam Pengembangan Sentral UMKM Ikan Pindang Desa Brondong Kabupaten Lamongan - Nurul Mey Syaroh; Ertien Rining Nawangsari (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This The purpose of this research is to describe the strategy of the Department of Fisheries in developing the central UMKM for boiled fish in Brondong Village, Lamongan Regency. In addition, this study aims to describe the successes and shortcomings of the Fisheries Service's strategy in developing boiled fish centers. This study used descriptive qualitative method. Researchers collected data, observations, interviews and documentation to obtain complete and detailed data. Subjects of this study were: (1)head of the Fisheries Service, (2) business development and quality development section, (3) actors and (4) buyers. The results of study using the SOAR model: 1)strengths aspect of pindang fish is that it is processed without using formalin, and the advantage is that pindangbrondong is fresh and tender when processed. 2)aspects of opportunities are carried out in terms of quality improvement, marketing, and branding. 3) aspect of aspiration conveyed by traders to Service regarding development, and traders conveying suggestions related to promotion. 4)aspect of result that is felt by traders is evidenced by increased income of traders, the PANDU SISKAMAYA and Pindang Hygienic innovations have been running smoothly, (UPI).